2014
DOI: 10.1111/and.12390
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of dietary-supplemented selenium and vitamin E in heat-induced apoptosis and oxidative stress in mice testes

Abstract: This study evaluated the role of selenium (0.5 ppm selenium/kg diet) and vitamin E (200 mg alpha-tocopherol/kg diet) on spermatogenesis after scrotal hyperthermia (42 °C, 30 min) in six different groups of male Balb/c mice; Control, Heat shock, Selenium, Selenium+heat shock, Vitamin E and Vitamin E+heat shock. Markers of the stress responses, hypoxia and oxidative stress, were evaluated in testis after the hyperthermic shock. Hyperthermia caused an elevated mRNA expression of hypoxia-inducible factor-1 alpha, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
4
27
0
Order By: Relevance
“…Selenium, a vital micronutrient, constitutes an essential component of GSH‐Px and selenoprotein P having ROS scavenging properties and can protect membrane lipids and macromolecules against oxidative damage. Accumulating evidences reveal that Se is required for maintenance of critical balance between germ cell death and proliferation during apoptosis in spermatogenesis (Kaur & Bansal, ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium, a vital micronutrient, constitutes an essential component of GSH‐Px and selenoprotein P having ROS scavenging properties and can protect membrane lipids and macromolecules against oxidative damage. Accumulating evidences reveal that Se is required for maintenance of critical balance between germ cell death and proliferation during apoptosis in spermatogenesis (Kaur & Bansal, ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Rayman () reviewed testis as a specific and privileged target of selenium that maintains normal spermatogenesis and male fertility. Se is proved to be beneficial in treating male infertility by improving sperm counts and motility through selenoproteins (Kaur & Bansal, ). In mammalian testis, the entire selenium content is associated with GSH‐Px selenoprotein and thus represents the crucial link between selenium, sperm quality and male fertility.…”
Section: Introductionmentioning
confidence: 99%
“…During reperfusion, nitric oxide (NO) and ROS production enhance germ cell‐specific necrosis. On the other hand, excessive generation of the ROS is tightly associated with the increased vulnerability of the cells to apoptosis (Kaur & Bansal, ; Mukherjee, Haldar, & Vishwas, ; Pazoki‐Toroudi, Ajami, et al., ; Pazoki‐Toroudi, Ajami, Babakoohi, et al., ). In present work, we evaluated the effect of capsaicin on pro‐apoptotic and anti‐apoptotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Erkekoglu et al (2012) reported that supplementation of Se to di(2-ethylhexyl) phthalate-treated rats lowered the activity of testicular germ cell apoptosis. In another study, a notable decrease in the apoptotic index of spermatogenic cells was recorded after scrotal hyperthermia in Se-supplemented mice (Kaur and Bansal, 2015).…”
Section: Discussionmentioning
confidence: 86%